Sustainable Islamic Fintech Ecosystem: A Comparative Analysis Of Indonesia And Bangladesh - firman, ahmad; Iskandar; Md. Mohi Uddin (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2025)
This article presents a comprehensive analysis of the integration of Financial Technology (FinTech) into the Islamic financial ecosystem in Indonesia, focusing on the paradox between its massive market potential and its still-low inclusive realization. The convergence of the world's largest Muslim population, a rapidly growing digital economy, and a developing sharia finance industry places Indonesia in a strategic position. However, behind the positive macro indicators, structural challenges are hindering widespread adoption, primarily due to low levels of Sharia financial literacy and inclusion. The key research gap identified is the lack of a systemic analysis linking the fragmentation of the regulatory framework, specifically the dualism between the Financial Services Authority (OJK) and the fatwas of the National Sharia Council-Indonesian Ulema Council (DSN-MUI), with the public trust deficit that hampers inclusion. Using qualitative methods through a comparative case study approach with Malaysia as a benchmark, this research finds that legal uncertainty arising from an incohesively integrated regulatory framework is the root cause of the low trust and effectiveness of literacy programs. These findings lead to strategic policy recommendations centered on regulatory harmonization to create legal certainty, a fundamental prerequisite for building a sustainable and inclusive Sharia FinTech ecosystem.